Product condition: an interdisciplinary concept for marketing management (Comunicação & Inovação, 2016)
The article presents an analysis of the relationship between subjectivity, virtual communication and management of web marketing to evaluate websites and blogs. The aim is to discuss the interdisciplinary dimensions of communication in the marketing management to map a product in cyberspace in a direct, clear and efficient way. Product of a quantitative and qualitative study that mapped 205 sites and blogs,describing their qualitative and quantitative characteristics. The result has enabled the creation of this evaluation instrument, interesting for both academics and professionals concerned with the metric to evaluate products in cyberspace.
Keywords: Marketing. Representation. Communication. State of product.